Spatiotemporal variation in marine litter distribution along the Bulgarian Black Sea sandy beaches: amount, composition, plastic pollution, and cleanliness evaluation - Bekova, Radoslava; Prodanov, Bogdan (Frontiers in Marine Science, 2024)
The threat of anthropogenic marine litter, particularly plastic pollution, to marine ecosystems and human health, has spurred mitigation initiatives and global scientific research. Following the Marine Strategy Framework Directive guidelines, this study evaluated marine litter distribution, cleanliness, and plastic pollution indices along Bulgarian Black Sea beaches in 2023. The survey integrates visual assessment, manual sampling, and drone mapping, distributing the beaches along the coastline to encompass a broader range, totaling 45, including 28 remote/natural, 10 semi-urban, and 7 urban beaches. Results indicate a 48% decrease in marine litter distribution on beaches from 1462 ± 147 items/100 m in 2021 to 753 ± 97 items/100 m in 2023, with Artificial polymer materials/plastic materials constituting 88.62% of the total litter amount. A comprehensive plastic macro litter pollution assessment was carried out along Bulgarian beaches using PAI for the first time. In 2023, the average cleanliness status of Bulgarian beaches was classified as “moderate” (CCI: 7.61 ± 1.00), with clean northern and central beaches contrasting with dirty southern beaches. Urbanized beaches were assessed with the highest level of pollution (PAIAV,23: 5.51; CCIAV,23: 18.16). In the long term, cleanliness and plastic pollution maintain “moderate” values with CCIAV,18-23: 8.81 ± 0.89, and PAIAV,18-23: 2.35 ± 0.32, persisting throughout the period, necessitating ongoing monitoring and intervention strategies. Despite identifying a significant number of clean beaches, none meet the EU threshold value of 20 litter items/100 m. This study highlights the urgent need for effective interventions to combat litter accumulation and plastic pollution, particularly in urban or semi-urban beaches, emphasizing multi-stakeholder collaboration for sustainable solutions and coastal ecosystem preservation.